Dr. Robert DeMott (San Jose, California; USA)
Publicity photo of Doctor Robert DeMott (interim director of the Steinbeck Center), Jack Douglas (head of Special Collections), and unidentified woman looking at recently purchased Steinbeck letters to Wanda van Brunt in Steinbeck Research Center, now the Martha Heasley Cox Center for Steinbeck Studies in its first location on the 6th floor of the Wahlquist Library, San Jose State.